An institutional perspective on borrowing discouragement among female-owned enterprises and the role of regional female empowerment - Forrester, Juanita Kimiyo; Neville, François (Journal of Business Venturing, 2021)
We develop an institutional perspective to examine the important, albeit largely overlooked, occurrence of borrowing discouragement for female-owned enterprises: the likelihood that they will not seek business financing because they believe their requests will be rejected. Given a prevailing business logic casting the field of entrepreneurship as largely male-typed, we theorize that female-owned enterprises will be more likely than their male-owned counterparts to exhibit borrowing discouragement. However, we also further propose that gender-based borrowing discouragement will be influenced by female empowerment levels in three distinct indicators of female empowerment that vary by geographic region within a society: social and economic autonomy, reproductive rights, and political participation. We find strong support for our predictions using a unique multi-sourced sample of 4090 small businesses operating in the United States.